Identification of cis-regulatory variations in the IL6R gene through the inheritance assessment of allelic transcription - Oh, Soo A.; Byun, Hyejin; Jang, Eunsu; Jeong, Sangkyun (Biochimica et biophysica acta, 2014)
The level of circulating interleukin-6 receptor in human blood varies depending on the genetic and/or physiological causes, and has been implicated in the development of chronic inflammatory diseases. The cis-regulatory effects of genetic variations on the transcription of interleukin-6 receptor gene, IL6R, were studied by assessing allelic transcriptions in the immortalized lymphocytes derived from unrelated and familial samples. The assays for allelic transcription in the cells from unrelated subjects demonstrated an extensive and variable range of allelic transcriptional imbalances, suggesting an operation of multiple cis-regulations with varying degrees on the locus. Analysis of the familial samples illustrated the Mendelian inheritance of allelic transcriptions, enabling us to assign each haplotype allele into one of the 3 transcriptional strengths. A comparison of the allele structures based on the transcriptional attributes highlighted 2 SNP variations, rs952146 and rs4845617, as being associated with higher allelic transcription. Consistently, lymphocytes that were homozygous for the 2 SNPs exhibited differences in their transcript levels depending on the haplotypes. Inheritance assessment of allelic transcription of IL6R identified 2 SNPs that are associated with transcriptional variation in cis. Our results not only demonstrate genetic variations that are associated with IL6R transcription in cis but also demonstrate an effective genetic approach for isolating cis-regulatory variations. •IL6R exhibited an extensive and wide range of allelic transcription imbalances.•Family study demonstrates the Medelian inheritance of IL6R allelic transcription.•Association of two SNP variations with higher allelic transcription was identified.